A new combination based on Myrcianthes irregularis (Myrtaceae) - A new genus for Ecuador - Landrum, L. (2011)
Myrcianthes irregularis McVaugh, a rare and endemic species of Ecuador, is transferred to Amomyrtella Kausel A key is provided for the two species of Amomyrtella.